Acid and alkali resistant explosion-proof ink and preparation method thereof

By adding low-melting point glass powder and acid- and alkali-resistant additives to the explosion-proof ink, the problem of insufficient acid- and alkali-resistant performance of traditional explosion-proof inks is solved, and higher acid- and alkali-resistant performance and wider application scenarios are achieved.

CN119432149AActive Publication Date: 2025-02-14TIANJIN SHIYU ELECTRONICS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411830745.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Traditional explosion-proof inks have poor acid and alkali corrosion resistance and cannot meet the demand for harsh outdoor environments of glass inks in new energy vehicles.

Method used

By improving the formulation of explosion-proof ink, low-melting point glass powder and acid- and alkali-resistant additives, specifically including bismuth oxide, boric acid, silicone chain molecular structure, etc., to form explosion-proof ink with excellent acid- and alkali-resistant properties.

Benefits of technology

It significantly improves the acid and alkali resistance of explosion-proof inks, extends the service life and use scenarios of glass, and ensures excellent explosion-proof and corrosion-resistant properties of the ink film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses acid-base-resistant explosion-proof ink and a preparation method thereof, and belongs to the technical field of modified ink, firstly, the acid-base-resistant explosion-proof ink is prepared from the following raw materials in parts by mass: 55 to 65 parts of low-melting-point glass powder, 17.5 to 22.5 parts of copper-chromium black agent, 17.5 to 22.5 parts of varnish, 8 to 10 parts of acid-base-resistant aid, 0.5 to 1 part of flatting agent and 0.5 to 1 part of defoaming agent. According to the acid-alkali-resistant explosion-proof ink and the preparation method thereof, the prepared acid-alkali-resistant explosion-proof ink is printed on glass through a silk-screen printing technology and then cured to form a layer of ink film, it is detected that the glass loaded with the ink film is cured to show excellent explosion-proof performance, and further, the anti-explosion effect is good. An ink film formed by curing the ink shows excellent acid and alkali resistance, and the service life and the use scene of cured glass loaded with the acid and alkali resistant explosion-proof ink are prolonged and expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified inks, and in particular relates to an acid-resistant, alkali-resistant and explosion-proof ink and a preparation method thereof. Background Art

[0002] In the application process of ink for tempered glass, the ink is first printed on the glass substrate using screen printing technology, then dried at high temperature, transferred to a high-temperature steel furnace for hot bending and sintering, and then cooled and formed to obtain tempered glass printed with glass ink. With the rapid development of the automotive industry and the improvement of consumers' demand for safety, explosion-proof ink has emerged. As the name suggests, explosion-proof ink is an ink material that can effectively prevent glass fragments from splashing when the glass is impacted by external forces and protect the safety of people in the car. This requires that the explosion-proof ink has excellent viscosity.

[0003] Traditional explosion-proof inks are mainly composed of additives such as low-melting glass powder, copper-chromium black agent, ink oil and leveling agent. Among them, low-melting glass powder is mainly composed of powders such as silicon dioxide, zinc oxide, and aluminum oxide. For example, the invention patent with application number CN201910326094.4 discloses a lead-free low-melting glass powder for automotive glass ink and its preparation method. The disclosed glass powder is mainly composed of silicon dioxide, boron oxide, bismuth oxide, zinc oxide, titanium oxide, aluminum oxide, etc. As one of the main components of glass ink, low-melting glass powder mainly functions to improve the bonding performance between ink and glass, and at the same time plays a role in heat conduction, oxygen isolation and toughening. However, the acid and alkali corrosion resistance of low-melting glass powder is poor. The performance of traditional explosion-proof inks can no longer meet the requirements of new energy vehicle glass inks for harsh outdoor environments. The technical problem of poor acidity and alkalinity has also become a key issue for the industry. Summary of the invention

[0004] The invention provides an acid- and alkali-resistant explosion-proof ink and a preparation method thereof, aiming to improve the acid- and alkali-resistant performance of the explosion-proof ink by improving the formula of the explosion-proof ink.

[0005] The purpose of the present invention can be achieved through the following technical solutions: An acid-proof and alkali-proof explosion-proof ink, comprising the following raw materials in parts by weight: 55-65 parts of low melting point glass powder; 17.5-22.5 parts of copper chromium black agent; Varnish 17.5-22.5 parts; 8-10 parts of acid and alkali resistant additives; 0.5-1 part of leveling agent; Defoaming agent 0.5-1 part; The acid and alkali resistant additive is prepared by the following steps: S1. Add diethylenetriamine to p-hydroxybenzoic acid, evacuate, and then heat to 145-155°C, stir and react at constant temperature for 2-3h, and continue to evacuate during the reaction. After completion, heat the system to 220-225°C, stir and react at constant temperature for 4-5h, and continue to evacuate during the reaction. After completion, cool to room temperature, collect the product, wash and dry the product to obtain an imidazole compound. In the above steps, the cyclization reaction of the terminal carboxyl group in p-hydroxybenzoic acid and diethylenetriamine is used to obtain the imidazole compound. The reaction process is as follows: .

[0006] S2, take anhydrous ethanol, fill it with nitrogen, add 2-bromo-5-acetylpyridine and imidazole compound, heat to produce reflux, keep heating reflux reaction for 4-5h, after completion, cool to room temperature, remove anhydrous ethanol by rotary evaporation, collect the product, and obtain an intermediate. In the above steps, Schiff base reaction is used to introduce pyridine ring and amide bond into imidazole compound to obtain intermediate. The reaction process is as follows: .

[0007] S3, take chloroform, fill it with nitrogen, add [3-(trimethoxysilyl)propyl]succinic anhydride and the intermediate thereto, stir at room temperature for 1-2h, add Amberlyst-15 ion exchange resin thereto, continue stirring for 1-2h after the addition is complete, raise the temperature to 65-70°C, stir and react at a constant temperature for 4-5h, cool to room temperature after completion, filter to remove the Amberlyst-15 ion exchange resin, and then remove the chloroform by rotary evaporation, collect the product, wash and dry the product to obtain an acid and alkali resistant additive, the above steps utilize the ring-opening reaction of the terminal hydroxyl group of the intermediate and the acid anhydride to obtain the acid and alkali resistant additive, the reaction process is as follows: .

[0008] Furthermore, the dosage ratio of p-hydroxybenzoic acid and diethylenetriamine in S1 is 1 mol:1.0-1.2 mol.

[0009] Furthermore, the usage ratio of anhydrous ethanol, 2-bromo-5-acetylpyridine and imidazole compound in S2 is 1L:0.4mol:82.1-82.5g.

[0010] Furthermore, the usage ratio of chloroform, [3-(trimethoxysilyl)propyl]succinic anhydride, intermediate, and Amberlyst-15 ion exchange resin in S3 is 1 L: 0.3 mol: 44-45 g: 30-40 g.

[0011] Furthermore, the low-melting-point glass powder comprises the following raw materials in parts by weight: 45-55 parts of bismuth oxide, 20-25 parts of boric acid, 12-15 parts of silicon dioxide, 7-8 parts of aluminum oxide, 5.5-7.5 parts of zirconium oxide, 4.5-5.5 parts of tin dioxide, 3-5 parts of titanium dioxide, 2-5 parts of lithium carbonate, and 2-5 parts of sodium carbonate.

[0012] Furthermore, the low melting point glass powder is prepared by the following steps: Weigh each raw material according to mass proportion, mix bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate and sodium carbonate, and place in a muffle furnace, heat from room temperature to 1120°C to 1150°C at a heating rate of 15 to 20°C / min, and then calcine at a constant temperature for 1 to 2 hours. After calcination, naturally cool to room temperature to obtain a glassy mixture, crush the glassy mixture through a 500-mesh sieve to obtain a low-melting-point glass powder.

[0013] Furthermore, the copper chromium black agent has a D 90 The particle size is 1.5~2.0μm.

[0014] Furthermore, the varnish comprises the following raw materials in parts by weight: 8-10 parts of acrylic resin, 100 parts of solvent, and 1-1.2 parts of dispersant HLN-1708.

[0015] Furthermore, the solvent is a mixture of diethylene glycol butyl ether and glycerol in a volume ratio of 8 to 10:1.

[0016] Furthermore, the varnish is prepared by the following steps: Weigh each raw material according to the mass part, add the acrylic resin and the dispersant HLN-1708 into the solvent with stirring, after the addition is completed, heat the system to 50-55°C, continue to stir at a constant temperature until the acrylic resin is completely dissolved, and then naturally cool to room temperature to obtain the varnish.

[0017] Furthermore, the leveling agent is one of leveling agent BYK-333 and leveling agent BYK-346.

[0018] Furthermore, the defoamer is one of defoamer BYK054, defoamer BYK057 and defoamer BYK1794.

[0019] Furthermore, the method for preparing the acid-proof, alkali-proof and explosion-proof ink comprises the following steps: Weigh each raw material according to the mass fraction, add low-melting-point glass powder and acid- and alkali-resistant additives to the varnish with stirring, stir at room temperature for 1 to 2 hours, then add leveling agent and defoaming agent thereto with stirring, stir at room temperature for 10 to 20 minutes. After completion, grind through an 800-mesh sieve to obtain acid- and alkali-resistant explosion-proof ink.

[0020] Beneficial effects of the present invention: The present invention provides an acid- and alkali-resistant explosion-proof ink and a preparation method thereof. The acid- and alkali-resistant explosion-proof ink prepared by the present invention is printed on glass by a screen printing process, and then a layer of ink film is formed after curing. After testing, the glass cured with the ink film exhibits excellent explosion-proof performance. Furthermore, the ink film formed by ink curing exhibits excellent acid- and alkali-resistant performance. The service life and use scenarios of the glass cured with the acid- and alkali-resistant explosion-proof ink are extended and expanded. The specific principles are as follows: The acid- and alkali-resistant explosion-proof ink provided by the present invention mainly comprises low-melting-point glass powder, acid- and alkali-resistant additives, varnish and other additives, wherein the low-melting-point glass powder is a Bi2O3-SiO2-B2O3 series low-melting-point glass powder, and other metal oxides are added. Bismuth oxide as the main raw material has excellent acid- and alkali-resistant corrosion performance. Among them, the acid and alkali resistant additive prepared by the present invention contains an imidazole ring, a pyridine ring, an amide bond and a siloxane chain molecular structure, wherein the imidazole ring and the pyridine ring structure have excellent acid and alkali corrosion resistance. Specifically, the imidazole ring and the pyridine ring themselves exhibit excellent acid and alkali corrosion resistance due to the presence of a conjugated system. Further, the nitrogen atoms contained in the imidazole ring and the pyridine ring can provide lone pairs of electrons, and these lone pairs of electrons can form coordination bonds with the metal ions of the metal oxide in the low-melting glass powder, thereby forming a protective film in the low-melting glass powder to prevent the corrosive medium from contacting the metal powder in the low-melting glass powder, thereby improving the acid and alkali corrosion resistance of the overall explosion-proof ink. At the same time, the siloxane chain molecular structure can further form a coordination effect with the metal ions of the metal oxide in the low-melting glass powder. At the same time, the siloxane chain molecular structure formed by hydrolysis of the siloxane chain molecular structure can improve the interaction between the acid and alkali resistant additive and the low-melting glass powder. At the same time, when the prepared ink is in service, the presence of the siloxane chain molecular structure can improve the bonding strength between the ink and the glass. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Example 1 Preparation of low melting point glass powder: First, the low melting point glass powder includes the following raw materials by weight: 45 parts of bismuth oxide, 20 parts of boric acid, 12 parts of silicon dioxide, 7 parts of aluminum oxide, 5.5 parts of zirconium oxide, 4.5 parts of tin dioxide, 3 parts of titanium dioxide, 2 parts of lithium carbonate, and 2 parts of sodium carbonate, wherein bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate, and sodium carbonate were all purchased from Sinopharm Chemical Reagent Co., Ltd.

[0023] Then, the low melting point glass powder is prepared by the following steps: The raw materials were weighed according to their mass parts, and bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate and sodium carbonate were mixed and placed in a muffle furnace. The temperature was raised from room temperature to 1150°C at a heating rate of 20°C / min, and then calcined at a constant temperature for 1h. After calcination, the mixture was naturally cooled to room temperature to obtain a glassy mixture. The glassy mixture was crushed and passed through a 500-mesh sieve to obtain a low-melting-point glass powder. The thermal expansion coefficient (25°C to 300°C) of the prepared low-melting-point glass powder was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany). -6 / ℃, the glass transition temperature is 427.2℃, and the glass softening temperature is 461.4℃.

[0024] Example 2 Preparation of low melting point glass powder: First, the low melting point glass powder includes the following raw materials by weight: 50 parts of bismuth oxide, 22 parts of boric acid, 14 parts of silicon dioxide, 8 parts of aluminum oxide, 7 parts of zirconium oxide, 5 parts of tin dioxide, 4 parts of titanium dioxide, 2.5 parts of lithium carbonate, and 2.5 parts of sodium carbonate, wherein bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate, and sodium carbonate were all purchased from Sinopharm Chemical Reagent Co., Ltd.

[0025] Then, the low melting point glass powder is prepared by the following steps: The raw materials were weighed according to their mass parts, and bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate and sodium carbonate were mixed and placed in a muffle furnace. The temperature was raised from room temperature to 1140°C at a heating rate of 15°C / min, and then calcined at a constant temperature for 2h. After calcination, the mixture was naturally cooled to room temperature to obtain a glassy mixture. The glassy mixture was crushed and passed through a 500-mesh sieve to obtain a low-melting-point glass powder. The thermal expansion coefficient (25°C to 300°C) of the prepared low-melting-point glass powder was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany). -6 / ℃, the glass transition temperature is 375.8℃, and the glass softening temperature is 408.1℃.

[0026] Example 3 Preparation of low melting point glass powder: First, the low melting point glass powder includes the following raw materials by weight: 55 parts of bismuth oxide, 25 parts of boric acid, 15 parts of silicon dioxide, 8 parts of aluminum oxide, 7.5 parts of zirconium oxide, 5.5 parts of tin dioxide, 5 parts of titanium dioxide, 5 parts of lithium carbonate, and 5 parts of sodium carbonate, wherein bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate, and sodium carbonate were all purchased from Sinopharm Chemical Reagent Co., Ltd.

[0027] Then, the low melting point glass powder is prepared by the following steps: The raw materials were weighed according to their mass parts, and bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate and sodium carbonate were mixed and placed in a muffle furnace. The temperature was raised from room temperature to 1120°C at a heating rate of 15°C / min, and then calcined at a constant temperature for 2h. After calcination, the mixture was naturally cooled to room temperature to obtain a glassy mixture. The glassy mixture was crushed and passed through a 500-mesh sieve to obtain a low-melting-point glass powder. The thermal expansion coefficient (25°C to 300°C) of the prepared low-melting-point glass powder was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany). -6 / ℃, the glass transition temperature is 401.3℃, and the glass softening temperature is 440.5℃.

[0028] Example 4 Preparation of varnish: First, the ink varnish includes the following raw materials by weight: 8 parts of acrylic resin, 100 parts of solvent, and 1 part of dispersant HLN-1708.

[0029] Among them, acrylic resin was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., item number L990045. The solvent was prepared by mixing diethylene glycol butyl ether and glycerol in a volume ratio of 8:1, and diethylene glycol butyl ether and glycerol were both purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0030] Then, the varnish is prepared by the following steps: Weigh each raw material according to the mass fraction, add the acrylic resin and the dispersant HLN-1708 into the solvent with stirring, after the addition is completed, heat the system to 50°C, continue to stir at a constant temperature until the acrylic resin is completely dissolved, and then naturally cool to room temperature to obtain the varnish.

[0031] Example 5 Preparation of varnish: First, the ink varnish includes the following raw materials by weight: 9 parts of acrylic resin, 100 parts of solvent, and 1.1 parts of dispersant HLN-1708.

[0032] Among them, acrylic resin was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., item number L990045. The solvent was prepared by mixing diethylene glycol butyl ether and glycerol in a volume ratio of 9:1, and diethylene glycol butyl ether and glycerol were both purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0033] Then, the varnish is prepared by the following steps: Weigh each raw material according to the mass fraction, add the acrylic resin and the dispersant HLN-1708 into the solvent with stirring, after the addition is completed, heat the system to 55° C., continue to stir at a constant temperature until the acrylic resin is completely dissolved, and then naturally cool to room temperature to obtain the varnish.

[0034] Example 6 Preparation of varnish: First, the ink varnish includes the following raw materials by weight: 10 parts of acrylic resin, 100 parts of solvent, and 1.2 parts of dispersant HLN-1708.

[0035] Among them, acrylic resin was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., item number L990045. The solvent was prepared by mixing diethylene glycol butyl ether and glycerol in a volume ratio of 10:1, and diethylene glycol butyl ether and glycerol were both purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0036] Then, the varnish is prepared by the following steps: Weigh each raw material according to the mass fraction, add the acrylic resin and the dispersant HLN-1708 into the solvent with stirring, after the addition is completed, heat the system to 55° C., continue to stir at a constant temperature until the acrylic resin is completely dissolved, and then naturally cool to room temperature to obtain the varnish.

[0037] Example 7 Preparation of acid and alkali resistant additives: S1. Add 1 mol of p-hydroxybenzoic acid (99.5%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring, and then add 1.0 mol of diethylenetriamine (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring. Evacuate reactor A, then heat to 145°C, and stir to react at constant temperature for 2 hours. Vacuum is continuously evacuated during the reaction. After completion, heat the system to 220°C, stir to react at constant temperature for 4 hours. Vacuum is continuously evacuated during the reaction. After completion, cool to room temperature, collect the product, wash the product three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then dry in a constant temperature drying oven at 40°C for 20 minutes. After completion, an imidazole compound is obtained.

[0038] S2. Add 1 L of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) into reactor B, fill it with nitrogen for protection, then add 0.4 mol of 2-bromo-5-acetylpyridine (97%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 82.1 g of imidazole compound into reactor B with stirring, heat reactor B to produce reflux, keep heating reflux reaction for 4 hours, cool to room temperature after completion, remove anhydrous ethanol by rotary evaporation, collect the product, and obtain the intermediate.

[0039] S3. Add 1L of chloroform (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, fill with nitrogen for protection, then add 0.3mol of [3-(trimethoxysilyl)propyl]succinic anhydride (95%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 44g of the intermediate to reactor C with stirring, stir at room temperature for 1h, then add 30g of Amberlyst-15 ion exchange resin (dry; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, and continue stirring for 1h after the addition is completed. After completion, the reactor C is heated to 65°C and stirred at a constant temperature for 4h. After completion, it is cooled to room temperature, the Amberlyst-15 ion exchange resin is filtered out, and the chloroform is removed by rotary evaporation. The product is collected, and the product is washed three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then placed in a constant temperature drying oven at 40°C for drying for 20min. After completion, an acid and alkali resistant additive is obtained.

[0040] Example 8 Preparation of acid and alkali resistant additives: S1. Add 1 mol of p-hydroxybenzoic acid (99.5%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring, and then add 1.1 mol of diethylenetriamine (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring. Evacuate reactor A, then heat to 150°C, and stir to react at constant temperature for 3 hours. Vacuum continuously during the reaction. After completion, heat the system to 224°C, stir to react at constant temperature for 5 hours. Vacuum continuously during the reaction. After completion, cool to room temperature, collect the product, wash the product three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then dry in a constant temperature drying oven at 45°C for 30 minutes. After completion, obtain an imidazole compound.

[0041] S2. Add 1 L of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) into reactor B, fill it with nitrogen for protection, then add 0.4 mol of 2-bromo-5-acetylpyridine (97%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 82.4 g of imidazole compound into reactor B with stirring, heat reactor B to produce reflux, keep heating reflux reaction for 5 hours, cool to room temperature after completion, remove anhydrous ethanol by rotary evaporation, collect the product, and obtain the intermediate.

[0042] S3. Add 1L of chloroform (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, fill with nitrogen for protection, then add 0.3mol of [3-(trimethoxysilyl)propyl]succinic anhydride (95%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 45g of the intermediate to reactor C with stirring, stir at room temperature for 2h, then add 40g of Amberlyst-15 ion exchange resin (dry; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, and continue stirring for 2h after the addition is completed. After completion, the reactor C is heated to 68°C and stirred at a constant temperature for 5h. After completion, it is cooled to room temperature, the Amberlyst-15 ion exchange resin is filtered out, and the chloroform is then removed by rotary evaporation. The product is collected, and the product is washed three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then placed in a constant temperature drying oven at 45°C for 30min. After completion, an acid and alkali resistant additive is obtained.

[0043] Example 9 Preparation of acid and alkali resistant additives: S1. Add 1 mol of p-hydroxybenzoic acid (99.5%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring, and then add 1.2 mol of diethylenetriamine (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) into reactor A with stirring. Evacuate reactor A, then heat to 155°C, and stir to react at constant temperature for 3 hours. Vacuum continuously during the reaction. After completion, heat the system to 225°C, stir to react at constant temperature for 5 hours. Vacuum continuously during the reaction. After completion, cool to room temperature, collect the product, wash the product three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then dry in a constant temperature drying oven at 50°C for 30 minutes. After completion, obtain an imidazole compound.

[0044] S2. Add 1 L of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) into reactor B, fill it with nitrogen for protection, then add 0.4 mol of 2-bromo-5-acetylpyridine (97%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 82.5 g of imidazole compound into reactor B with stirring, heat reactor B to produce reflux, keep heating reflux reaction for 5 hours, cool to room temperature after completion, remove anhydrous ethanol by rotary evaporation, collect the product, and obtain the intermediate.

[0045] S3. Add 1L of chloroform (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, fill with nitrogen for protection, then add 0.3mol of [3-(trimethoxysilyl)propyl]succinic anhydride (95%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 45g of the intermediate to reactor C with stirring, stir at room temperature for 2h, then add 40g of Amberlyst-15 ion exchange resin (dry; purchased from Sinopharm Chemical Reagent Co., Ltd.) to reactor C, and continue stirring for 2h after the addition is completed. After completion, the reactor C is heated to 70°C and stirred at a constant temperature for 5h. After completion, it is cooled to room temperature, the Amberlyst-15 ion exchange resin is filtered out, and the chloroform is then removed by rotary evaporation. The product is collected, and the product is washed three times with anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.), and then placed in a constant temperature drying oven at 50°C for drying for 30min. After completion, an acid and alkali resistant additive is obtained.

[0046] Example 10 Preparation of acid and alkali resistant explosion-proof ink: First, the acid and alkali resistant explosion-proof ink includes the following raw materials by weight: 55 parts of the low-melting-point glass powder prepared in Example 1; 22.5 parts of copper chrome black agent; 22.5 parts of the varnish prepared in Example 4; 8 parts of the acid and alkali resistant additive prepared in Example 7; 0.5 parts of leveling agent; 0.5 parts of defoaming agent.

[0047] Among them, D of copper chrome black agent 90 The particle size is 2.0μm.

[0048] Among them, the leveling agent is leveling agent BYK-333.

[0049] Among them, the defoaming agent is defoaming agent BYK054.

[0050] Then, the preparation method of the acid-proof and alkali-proof explosion-proof ink comprises the following steps: Weigh each raw material according to the mass fraction, add the low-melting-point glass powder prepared in Example 1 and the acid- and alkali-resistant additive prepared in Example 7 to the varnish prepared in Example 4, stir at room temperature for 1 hour, then add the leveling agent and defoaming agent thereto, stir at room temperature for 10 minutes, and after completion, grind through an 800-mesh sieve to obtain acid- and alkali-resistant explosion-proof ink.

[0051] Embodiment 11 Preparation of acid and alkali resistant explosion-proof ink: First, the acid and alkali resistant explosion-proof ink includes the following raw materials by weight: 60 parts of the low-melting-point glass powder prepared in Example 2; 20 parts of copper chrome black agent; 20 parts of the varnish prepared in Example 5; 10 parts of the acid and alkali resistant additive prepared in Example 8; 1 part of leveling agent; 1 part defoamer.

[0052] Among them, D of copper chrome black agent 90 The particle size is 1.5μm.

[0053] Among them, the leveling agent is leveling agent BYK-346.

[0054] Among them, the defoaming agent is defoaming agent BYK057.

[0055] Then, the preparation method of the acid-proof and alkali-proof explosion-proof ink comprises the following steps: Weigh each raw material according to the mass fraction, add the low-melting-point glass powder prepared in Example 2 and the acid- and alkali-resistant additive prepared in Example 8 to the varnish prepared in Example 5, stir at room temperature for 2 hours, then add the leveling agent and defoaming agent thereto, stir at room temperature for 20 minutes, and after completion, grind through an 800-mesh sieve to obtain an acid- and alkali-resistant explosion-proof ink.

[0056] Example 12 Preparation of acid and alkali resistant explosion-proof ink: First, the acid and alkali resistant explosion-proof ink includes the following raw materials by weight: 65 parts of the low-melting-point glass powder prepared in Example 3; 17.5 parts of copper chrome black agent; 17.5 parts of the varnish prepared in Example 6; 10 parts of the acid and alkali resistant additive prepared in Example 9; 1 part of leveling agent; 1 part defoamer.

[0057] Among them, D of copper chrome black agent 90 The particle size is 1.5μm.

[0058] Among them, the leveling agent is leveling agent BYK-346.

[0059] Among them, the defoaming agent is BYK1794.

[0060] Then, the preparation method of the acid-proof and alkali-proof explosion-proof ink comprises the following steps: Weigh each raw material according to the mass fraction, add the low-melting-point glass powder prepared in Example 3 and the acid- and alkali-resistant additive prepared in Example 9 to the varnish prepared in Example 6, stir at room temperature for 2 hours, then add the leveling agent and defoaming agent thereto, stir at room temperature for 20 minutes, and after completion, grind through an 800-mesh sieve to obtain an acid- and alkali-resistant explosion-proof ink.

[0061] Comparative Example 1 Comparative Example 1 is the control group of Example 11, in which the acid and alkali resistant additive prepared in Example 8 in Example 11 is replaced by the intermediate prepared in step S2 in Example 8, and the remaining raw materials, raw material amounts and preparation steps remain the same as in Example 11, and finally an explosion-proof ink is obtained.

[0062] Comparative Example 2 Comparative Example 2 is the control group of Example 11, in which the acid and alkali resistant additive prepared in Example 8 in Example 11 is removed, and the remaining raw materials, raw material amounts and preparation steps are kept the same as in Example 11, and finally an explosion-proof ink is obtained.

[0063] Test Example 1 The performance test of the acid-base resistant explosion-proof ink / explosion-proof ink prepared in Examples 10 to 12 and Comparative Examples 1 to 2 was performed. The performance test process is as follows, and the test results are shown in Table 1: Preparation of ink samples: The acid and alkali resistant explosion-proof ink / explosion-proof ink prepared in Examples 10 to 12 and Comparative Examples 1 to 2 were screen-printed (250 mesh, pore size 57 μm) on both sides of a glass substrate (40 mm × 40 mm × 5 mm), and the thickness of the ink layer was controlled at 20 μm. The glass substrate printed with the ink layer was placed at 720°C for 200 seconds for tempering treatment. After the treatment, it was cooled to room temperature to obtain an ink sample.

[0064] Adhesion: The adhesion level test was carried out according to the method specified in the national standard ISO2409 "Paints and varnishes - Cross-cut test". Specifically, the ink layer on the surface of the ink sample was tested with a cross-cut knife (Model 5152, purchased from BYK, Germany). The blade scratched the ink layer of the ink sample at a vertical angle of 90° to form a tic-tac-toe cross-cut line. The lines were then quickly adhered and peeled off with tape to observe the shedding of the ink layer. The adhesion level decreased from 0 to 5, and no shedding occurred on the surface of the ink layer at level 0.

[0065] Explosion-proof performance: Refer to the test method specified in the national standard GB / T 39814-2021 "Ultra-thin glass impact strength test method - falling ball impact method" to measure the maximum impact height of the ink sample. At the same time, the damage state of the ink sample at the maximum impact height is recorded, as shown in Table 1 below. The steel ball used complies with the provisions of GB / T308.1, and the mass of the steel ball is 32g and the diameter is 19.844mm.

[0066] Acid resistance: Accurately weigh the mass of the ink sample, record it as W0, and then soak the ink sample in 0.05 mol / L H2SO4 solution at 80℃ for 72h. After soaking, take it out and cool it to room temperature. Wipe the liquid on the surface of the ink sample with absorbent paper and dry it to obtain the acid-soaked ink sample. Prepare to weigh the mass of the acid-soaked ink sample, record it as W1, and then calculate the acid-resistant mass loss rate (g / cm2) by the following formula (1): 2 ): Acid resistance mass loss rate = (W0-W1) / S (1); In formula (1), S is the surface area of ​​the ink layer in the ink sample, in cm 2 ; Alkali resistance: Accurately weigh the mass of the ink sample, recorded as W0, and then soak the ink sample in a 0.05 mol / L NaOH solution at 80°C for 80 hours. After soaking, take it out and cool it to room temperature. Wipe the liquid on the surface of the ink sample with absorbent paper and dry it to obtain a natron ink sample. Prepare to weigh the mass of the natron ink sample, recorded as W1, and then calculate the alkali resistance mass loss rate (g / cm 2 ): Alkali resistance mass loss rate = (W0-W1) / S (2); In formula (2), S is the surface area of ​​the ink layer in the ink sample, in cm 2 .

[0067] Table 1 Performance test results

[0068] It can be seen from Table 1 that adding the acid and alkali resistance additive prepared by the present invention can significantly improve the acid and alkali resistance of the prepared explosion-proof ink.

[0069] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A kind of acid and alkali resistant explosion-proof ink, characterized in that: Including the following raw materials by weight: 55-65 parts of low melting point glass powder; 17.5-22.5 parts of copper chromium black agent; Varnish 17.5-22.5 parts; 8-10 parts of acid and alkali resistant additives; 0.5-1 part of leveling agent; Defoaming agent 0.5-1 part; The acid and alkali resistant additive is prepared by the following steps: S1. Add diethylenetriamine to p-hydroxybenzoic acid, evacuate, and then heat to 145-155°C, stir and react at constant temperature for 2-3 hours, and continue to evacuate during the reaction. After completion, heat the system to 220-225°C, stir and react at constant temperature for 4-5 hours, and continue to evacuate during the reaction. After completion, cool to room temperature, collect the product, and wash and dry the product to obtain an imidazole compound; S2, take anhydrous ethanol, fill it with nitrogen, add 2-bromo-5-acetylpyridine and imidazole compound, heat to reflux, keep heating reflux reaction for 4-5h, after completion, cool to room temperature, remove anhydrous ethanol by rotary evaporation, collect the product, and obtain an intermediate; S3. Take chloroform, fill it with nitrogen, add [3-(trimethoxysilyl)propyl]succinic anhydride and the intermediate thereto, stir at room temperature for 1 to 2 hours, add Amberlyst-15 ion exchange resin thereto, continue stirring for 1 to 2 hours after the addition is completed, raise the temperature to 65 to 70°C, stir and react at a constant temperature for 4 to 5 hours, cool to room temperature after completion, filter out the Amberlyst-15 ion exchange resin, and then rotary evaporate to remove the chloroform, collect the product, and wash and dry the product to obtain an acid and alkali resistant additive.

2. The acid-proof and alkali-proof explosion-proof ink according to claim 1, characterized in that: The dosage ratio of p-hydroxybenzoic acid and diethylenetriamine described in S1 is 1 mol: 1.0-1.2 mol; the dosage ratio of anhydrous ethanol, 2-bromo-5-acetylpyridine and imidazole compound described in S2 is 1L: 0.4 mol: 82.1-82.5 g; the dosage ratio of chloroform, [3-(trimethoxysilyl)propyl] succinic anhydride, intermediate and Amberlyst-15 ion exchange resin described in S3 is 1L: 0.3 mol: 44-45 g: 30-40 g.

3. The acid-proof and alkali-proof explosion-proof ink according to claim 1, characterized in that: The low melting point glass powder comprises the following raw materials in parts by weight: 45-55 parts of bismuth oxide, 20-25 parts of boric acid, 12-15 parts of silicon dioxide, 7-8 parts of aluminum oxide, 5.5-7.5 parts of zirconium oxide, 4.5-5.5 parts of tin dioxide, 3-5 parts of titanium dioxide, 2-5 parts of lithium carbonate, and 2-5 parts of sodium carbonate.

4. The acid-proof and alkali-proof explosion-proof ink according to claim 3, characterized in that: The low melting point glass powder is prepared by the following steps: Weigh each raw material according to mass proportion, mix bismuth oxide, silicon dioxide, boric acid, aluminum oxide, zirconium oxide, tin dioxide, titanium dioxide, lithium carbonate and sodium carbonate, and place in a muffle furnace, heat from room temperature to 1120°C to 1150°C at a heating rate of 15 to 20°C / min, and then calcine at a constant temperature for 1 to 2 hours. After calcination, naturally cool to room temperature to obtain a glassy mixture, crush the glassy mixture through a 500-mesh sieve to obtain a low-melting-point glass powder.

5. The acid-proof and alkali-proof explosion-proof ink according to claim 1, characterized in that: The copper chrome black agent D 90 The particle size is 1.5~2.0μm.

6. The acid-proof and alkali-proof explosion-proof ink according to claim 1, characterized in that: The varnish comprises the following raw materials in parts by weight: 8-10 parts of acrylic resin, 100 parts of solvent, 1-1.2 parts of dispersant HLN-1708.

7. The acid-proof and alkali-proof explosion-proof ink according to claim 6, characterized in that: The solvent is prepared by mixing diethylene glycol butyl ether and glycerol in a volume ratio of 8 to 10:

1.

8. The acid-proof and alkali-proof explosion-proof ink according to claim 6, characterized in that: The varnish is prepared by the following steps: Weigh each raw material according to the mass part, add the acrylic resin and the dispersant HLN-1708 into the solvent with stirring, after the addition is completed, heat the system to 50-55°C, continue to stir at a constant temperature until the acrylic resin is completely dissolved, and then naturally cool to room temperature to obtain the varnish.

9. The acid-proof, alkali-proof and explosion-proof ink according to claim 1, characterized in that: The leveling agent is one of leveling agent BYK-333 and leveling agent BYK-346; the defoaming agent is one of defoaming agent BYK054, defoaming agent BYK057 and defoaming agent BYK1794.

10. A method for preparing an acid-proof, alkali-proof and explosion-proof ink according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh each raw material according to the mass fraction, add low-melting-point glass powder and acid- and alkali-resistant additives to the varnish with stirring, stir at room temperature for 1 to 2 hours, then add leveling agent and defoaming agent thereto with stirring, stir at room temperature for 10 to 20 minutes. After completion, grind through an 800-mesh sieve to obtain acid- and alkali-resistant explosion-proof ink.

Citation Information

Patent Citations

  • Lead-free low-melting-point glass powder used for automotive glass ink and preparation method of glass powder

    CN109867449A

  • Acid-and-alkali-resistant environment-friendly ink for automotive windscreen and preparing method thereof

    CN105623376A

  • Inking process of automobile glass

    CN110563346A

  • Acid and alkali resistant automobile glass ink and preparation method thereof

    CN110607091A

  • Silver-loaded antibacterial master batch and application thereof

    CN114350070A